The effect of leaf area to crop weight ratios on fruit quality and performance of grapevine (Vitis vinifera cv. Pinot Noir) - Pasch, Ludwig Anselm (2017)
Mestrado Vinifera EuroMaster - Instituto Superior de Agronomia